The Effect of Audit Method Preference, Attitude Towards Technology, and Organizational Support on Auditor Performance - Raddina Sofiyulhaq, Kyesa Djibrilia; Aresteria, Maya (Tax Accounting Applied Journal, 2025)
This study aims to analyze the influence of audit methods, attitudes toward technology, and organizational support on auditor performance. The rapid development of digitalization in the auditing environment requires auditors not only to master manual audit techniques but also to adapt to technology and operate within a supportive organizational structure. Auditor performance is a key indicator of audit effectiveness and accountability.This research employs a quantitative approach using an associative method. Data were collected through questionnaires distributed to 100 auditors working at Public Accounting Firms (KAP) and Regional Inspectorates in the city of Semarang. Statistical testing was conducted using EViews software, including descriptive statistics, classical assumption tests, and multiple linear regression to examine the effect of independent variables on the dependent variable. The independent variables include audit method (X1), attitude toward technology (X2), and organizational support (X3), while the dependent variable is auditor performance (Y).The results show that all three independent variables, both partially and simultaneously, have a significant positive effect on auditor performance. Auditors who use appropriate audit methods, demonstrate positive attitudes toward technology, and receive strong organizational support tend to exhibit higher performance. These findings are consistent with Expectancy Theory, which explains that work behavior is influenced by perceptions of the tools used, the support received, and the expected results it can be concluded that the increase in auditor performance is not only determined by individual capabilities but also by the selection of appropriate work strategies, readiness for technological change, and the level of organizational support provided to enable optimal performance.